Primary liposarcoma of the uterus with MDM2 negative - Shufei Wei; Lushun Zhang; Yongliang Han; Liangliang Wang (Indian Journal of Pathology and Microbiology)
Liposarcoma is one of the most common soft-tissue sarcomas that originates from adipose tissue. Primary uterine liposarcoma is extremely rare. With the MDM2, negative is even rarer. We report a 37-year-old woman presented with lower abdominal discomfort and increase in vaginal secretions for more than 2 months. The ultrasonography revealed a hypoechoic mass sized 81 × 73 × 67 mm in the right adnexal area. Histopathologically, the neoplasm was mainly composed of mature adipose tissue, a small number of scattered lipoblasts, and the spindle cell which with mild atypia. Immunohistochemistry showed that the tumor cells were positive for CDK4 but negative for MDM2, and FISH analysis showed no MDM2 amplification. The patient only underwent tumor excision and is currently doing well.